Single Stage Urethroplasty for Proximal Hypospadias with Chordee - Hassan, MK; Paul, AC; Khair, MA; Saha, RK; Hanif, A; Chowdhury, ASMJ (Faridpur Medical College Journal, 2011)
Proximal hypospadias with chordee usually requires two stage procedures: 1st stage is orthoplasty and ventral parking of prepucial skin and 2nd stage is urethroplasty after 6 months of 1st stage. The aim of this study is to describe and report the outcome of a single stage repair- Koyanagi Nanamura procedure for proximal hypospadias with chordee. Between January 2006 to December 2010, 44 boys with proximal hypospadias underwent repair using the Koyanagi Nanamura technique in Paediatric Surgery Department of Faridpur Medical College Hospital and Dhaka Medical College Hospital. The boys' age ranged from 1 to 7 years. The technique employs the use of lateral penile skin and extends into the inner preputial skin. This flap enjoys double blood supply from the base of the meatus as well as the preputial vessels. Follow-up period was 6 months. Satisfactory results were obtained in 39 (88.6%) patients. Three patients developed fistulae. Two patients developed meatal stenosis. Results were considered satisfactory when the boy achieves a glanular meatus, single forward stream, unimpeded voiding, good cosmesis, and no need for secondary surgery for the urethra. Koyanagi Nanamura procedure is a reliable procedure in which the lateral flaps have dual blood supply, which produces good results (88.6%) and is suitable for proximal forms of hypospadias with chordee. Key words: Hypospadias; Chordee; Fistula; Penis DOI: http://dx.doi.org/10.3329/fmcj.v6i2.9202 FMCJ 2011; 6(2): 66-69